Potential of natural repellents methylanthranilate and anthraquinone applied on maize seeds and seedlings against house sparrow (Passer domesticus) in captivity - Ahmad,S. (2018)
Abstract Various bird pests caused severe economic losses to valuable crops and fruit orchards all over the world. Among the birds, house sparrow is also considered to cause heavy plunder, not only to seeds of crops but also seedlings especially in organic farming. In present study two bird repellents, methylanthranilate and anthraquinone tested against house sparrows on maize seeds and seedlings in aviary conditions. Trial group in aviary-I, the treated maize seeds and seedlings with different doses of both bird repellents, control group in aviary-II, untreated seeds and seedlings were provided for three hours in the early morning. In each aviary, two closed circuit cameras were also installed to monitor the behavioral responses against different concentrations of both chemical repellents. Statistical analysis showed that there existed highly significant (P<0.01) variations among the trial and control groups for seeds and seedlings. By comparing both repellents, significant (P<0.05) differences were detected and anthraquinone showed better efficacy when compared to methylanthranilate, but in maize seedlings both repellents equal repellent properties. Non-significant (P>0.05) differences were observed in different grading of both natural chemical repellents for maize seeds while significant (P<0.05) variations were noticed for maize seedlings when provided to sparrows. By videotaped behavior sparrows presented manifest head juddering and feather upsetting activities by consumption of treated seeds and seedlings with higher concentrations of both natural bird repellents.